2023
DOI: 10.1097/qco.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Neurobrucellosis

Abstract: Purpose of reviewBrucellosis is one of the most common zoonosis worldwide, affecting 500 000 people, annually. Neurobrucellosis incidence is approximately 4%, and it is almost always heterogeneous. As there are no typical clinical features, its diagnosis is frequently misdiagnosing by other infections.Recent findingsNeurobrucellosis picture includes meningitis, meningoencephalitis, encephalitis, cranial neuropathies, intracranial hypertension, sinus thrombosis, hemorrhages radiculitis, peripheral neuropathy, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Occurs in 1–5% of those with tuberculosis [ 12 ]. While the incidence of neurobrucellosis in brucellosis is about 4% [ 13 ]. In the early stage of these disease, symptoms such as fever, headache and sometimes nausea and vomiting may be present.…”
Section: Discussionmentioning
confidence: 99%
“…Occurs in 1–5% of those with tuberculosis [ 12 ]. While the incidence of neurobrucellosis in brucellosis is about 4% [ 13 ]. In the early stage of these disease, symptoms such as fever, headache and sometimes nausea and vomiting may be present.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Brucella infection can be confirmed through culture, serological testing, or nucleic acid amplification tests. Previous studies have shown that CSF and venous blood cultures have a low positive rate and are time consuming ( 13 ). However, with the advancement of automated blood culture systems, Brucella can now be detected in over 95% of blood cultures collected from patients with acute brucellosis within 1 week ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurobrucellosis (NB) refers to the involvement of the nervous system and occurs in 3-7% of all patients with brucellosis ( Haji-Abdolbagi et al., 2008 ). The most frequently observed manifestations of neurobrucellosis include meningitis and meningoencephalitis, myelitis, craniocerebral diseases, peripheral neuropathy, and others ( Soares et al., 2023 ). NB has a slow onset., The effects of brucellosis on the nervous system may result from persistent intracellular microorganisms ( Dando et al., 2014 ), or infection may trigger immune mechanisms, resulting in inflammatory immune responses of cytokines or endotoxins and leading to myelopathy and/or demyelination inflammatory central and peripheral demyelination ( Ceran et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%